Disruption of endothelial Pfkfb3 ameliorates diet-induced murine insulin resistance. Issue 3 (14th July 2021) - Yang, Qiuhua; Xu, Jiean; Ma, Qian; Liu, Zhiping; Zhou, Yaqi; Cai, Yongfeng; Mao, Xiaoxiao; Stepp, David; Weintraub, Neal; Fulton, David J; Hong, Mei; Huo, Yuqing
Abstract : Overnutrition-induced endothelial inflammation plays a crucial role in high-fat diet (HFD)-induced insulin resistance in animals. Endothelial glycolysis plays a critical role in endothelial inflammation and proliferation, but its role in diet-induced endothelial inflammation and subsequent insulin resistance has not been elucidated. PFKFB3 is a critical glycolytic regulator, and its increased expression has been observed in adipose vascular endothelium of C57BL/6J mice fed with HFD in vivo, and in palmitate (PA)-treated primary human adipose microvascular endothelial cells (HAMECs) in vitro . We generated mice with Pfkfb3 deficiency selective for endothelial cells to examine the effect of endothelial Pfkfb3 in endothelial inflammation in metabolic organs and in the development of HFD-induced insulin resistance. EC Pfkfb3- deficientmice exhibited mitigated HFD-induced insulin resistance, including decreased body weight and fat mass, improved glucose clearance and insulin sensitivity, and alleviated adiposity and hepatic steatosis. Mechanistically, cultured PFKFB3 knockdown HAMECs showed decreased NF-κB activation induced by PA, and consequent suppressed adhesion molecule expression and monocyte adhesion. Taken together, these results demonstrate that increased endothelial PFKFB3 expression promotes diet-induced inflammatory responses and subsequent insulin resistance, suggesting that endothelial metabolic alteration plays an important role in the development of insulin resistance.